LA NOCIÓN DE TÍTULO VALOR - Zegarra Mulánovich, Álvaro (Revista de Derecho, 2022)
This paper rests on the main proposals on the concept of negotiable instruments (títulos valores, Wertpapiere, titoli di credito) made in the past by German (with its “broad notion”) and Italian (with its “restrictive notion”) legal literatures. It analyses their reception in Peruvian statute and their application in case law, in connection to the so-called “principles” or “characteristic traits” of negotiable instruments. In this sense, the paper examines the specific connection of the various aforementioned characters, and in particular those of “incorporation” and “circulatory scope”, with the notion of negotiable instrument, and attempts to justify why only some of them (and which) make part of their definition, whereas others don’t.